Relationship between fiscal expenditure and stat support projects to develop the investment in Algeria (Journal of Economic Additions, 2020)
The aim of this study is show the relationship between fiscal expenditure with stat support projects in development the investment , through studing the most important of fiscal policy tools , which use by governments in order to stimulate priority investment activities, through  presents the most important type of fiscal expenditure and the methods of cost estimation of fiscal expenditure     As result of this research we  that the investment is one of the means of operating of funds for economic and social benefit, as it is clear that its importance lies in being one of the means by which to expand the institutions and the formation of wealth in addition to making a profit. The relationship between tax and investment is reflected in the fiscal expenditure policy, which in turn contributes to the development of investment.key words: Tax expenditure ; Investment ;Tax Exemptions; Tax Discounts ; Tax Loan ; Tax Delay. Classification Jel H21  H24  H50  H71